Study of Characteristics of Bitumen and Aggregate with Use of Plastic Waste - Bhusal, Gaurav; Koirala, Badal; Kharbuja, Sunita (International Journal on Engineering Technology, 2024)
Plastic is everywhere, and its use in different forms is increasing day by day despite discouragement from the government. Plastic waste disposal is a global issue since they are non-biodegradable and toxic in burning. Plastic pollution threatens food quality, human health, sanitation, and the ecosystem and contributes to climate change. The usage of plastic waste in elements (bitumen and aggregate) used in road construction was the main objective of this study. With use of appropriate plastic waste in building of road would not only reduce material cost but also contributes in solving plastic waste management issue. Nepal being a developing country with low Gross Domestic Product (GDP) where most of the districts are still deprived of good flexible pavement networks, plastic modified roads could be a value engineering and economic solution. The paper highlights by which method plastic waste can be used effectively in road construction by performing different experimental tests reflecting the characteristics of bitumen and aggregate on addition of plastic. The study has determined the penetration, softening point, ductility values of bitumen and impact and abrasion values of aggregate in addition to different percentage of plastic waste. According to the study, bitumen’s penetration and ductility value drop with increasing plastic content, making it better suited for usage in warmer climates, but its softening point rises, ensuring a stronger resistance to flow in services. Comparably, when in aggregate plastic content rises, both its AIV value and its LA abrasion value fall, enhancing the aggregate’s toughness and ability to endure greater wear and tear.